Предмет: Алгебра,
автор: lovely270693
(3x-2)(2x-4)=0 решить уравнение как?
Ответы
Автор ответа:
0
делим уравнение на 2 части
3х-2=0 3х=0+2 3х=2 х=2/3 х=0,(6)
2х-4=0 2х=0+4 2х=4 х=4/2 х=2
х= {0.(6) , 2}
3х-2=0 3х=0+2 3х=2 х=2/3 х=0,(6)
2х-4=0 2х=0+4 2х=4 х=4/2 х=2
х= {0.(6) , 2}
Автор ответа:
0
6x^2-12x-4x+8=0
6x^2-16x+8=0 разделим на 2 для упрощения
3x^2-8x+4=0
D=-8^2*-4*3*4=64-48=16
x1=8+4/6=2
x2=8-4/6=2/3
6x^2-16x+8=0 разделим на 2 для упрощения
3x^2-8x+4=0
D=-8^2*-4*3*4=64-48=16
x1=8+4/6=2
x2=8-4/6=2/3
Похожие вопросы
Предмет: Английский язык,
автор: CenterNew
Предмет: Биология,
автор: gusik1313
Предмет: История,
автор: vikazadoroznyak
Предмет: Литература,
автор: ccheater
Предмет: Химия,
автор: asdfasers